Effect of Immersion Time and Packaging Type on the Quality of Curly Red Chili Coated with Chitosan–Aloe vera - Muhammad Rifqi; Sherina Zahran Tiara; Tiana Fitrilia (The University of Lampung, 2026)
Curly red chili has a short shelf life such that post-harvest handling techniques, including edible coatings, are essential. This study aimed to determine the effect of edible coating immersion time and packaging type on the shelf life of curly red chili. The experiment used a completely randomized design (CRD) with two factors: immersion duration (5, 7.5, and 10 minutes) and polypropylene (PP) plastic packaging type (non-perforated and perforated). Data were analyzed using a Two-Way ANOVA, followed by Duncan's Range Multiple Test (DMRT) at a 95% confidence level. The parameters measured included weight loss, moisture content, vitamin C content, and respiration rate. The optimal treatment was A1B2 (5-minute immersion with perforated PP packaging), which achieved the highest vitamin C content (460.32 mg/100g), the lowest respiration rate (1.89 mg CO₂.kg–1.h–1), a weight loss of 26.82%, and a moisture content of 67.73%. Although weight loss in A1B2 was higher than in non-perforated packaging treatments, vitamin C and respiration rate were prioritized as key nutritional and metabolic quality indicators. Compared to control in perforated packaging (A0B2), treatment A1B2 yielded 24.60% higher vitamin C retention, demonstrating the added value of the chitosan–Aloe vera coating